Intelligence at the Learneds: The RCMP, the Learneds, and the Canadian Historical Association - Hewitt, Steve (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1998)
AbstractMuch of the history of Royal Canadian Mounted Police's (RCMP) security intelligence role has ignored domestic counter-subversion work in favour of more glamorous counter-espionage operations. “Intelligence at the Learneds: The RCMP, the Learneds, and the Canadian Historical Association” examines one small part of that neglected counter-subversion past. For nearly twenty-five years, from 1960 to 1983, members of the RCMP secretly covered and reported upon various meetings of the Learned Societies. Initially attracted by the presence of communists, by the 1970s the RCMP had changed its focus to members of the so-called New Left. Hounded by criticism in the aftermath of the McDonald Commission's final report in 1981, Mounties returned to monitoring communists. Mounted Police coverage ended in 1984, when the Canadian Security Intelligence Service (CSIS) replaced the Security Service. The paper concludes with a suggestion that CSIS may not be as free from its RCMP ancestor as some would suggest.